Synthesis and Consolidation of the Aluminosilicate Mineral Anorthite - Lauren E Eccles (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2022)
Solid-state ceramic synthesis is a fabrication process involving high temperature reactions of solid component powders and is used to prepare materials with novel and advanced properties. Regarding synthetic mineral ceramics, the solid-state process makes it possible to design synthetic minerals with specific compositions and properties not commonly found in their natural, comparatively impure, counterparts. This study focuses on the synthesis of the feldspar anorthite, CaAl2Si2O8, via solid-state procedures and the densification of the synthesized powders using the technique of uniaxial hot-pressing. Constituent powders of aluminum sesquioxide (Al2O3), silicon dioxide (SiO2), and calcium monoxide (CaO) were subjected to bulk powder milling, calcination, powder consolidation, and pressure-less sintering, so as to produce high purity, homogeneous materials. The fabricated anorthite samples were then hot-pressed to produce solid, high-density anorthite pellets. The densification of solid anorthite samples was monitored using geometric density measurements. The composition and microstructure of the pressure-less sintered and hot-pressed samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDXS). It was shown that anorthite was successfully synthesized and that uniaxial hot-pressing of anorthite powder yielded a solid pellet with a density greater than 90% of the theoretical density of CaAl2Si2O8.